Case Study of the Institutional Management Policy National Laboratory Post Transition the National Institute of Health Research and Development (NIHRD) - Fauzul Muna; Edy Sutrisno; Bambang Giyanto (International Journal of Economics Development Research (IJEDR), 2023)
This research was conducted to identify institutional structuring policy in National Laboratory, include external factor that influence the implementation of these policie and the strategies required by the National Laboratory after the institutional structuring process. The method used in this research is qualitative method, namely data collection through case study and in-depth interviews also conducted PEST Analysis. The results of this research show that the institutional management policy at the National Laboratory has not work well due to changes in business process which have changed all organizational tasks and functions including duties, structure and human resources. Institutional management policies are influenced by external organizational factors, such as political, environmental, social, and technical factors. Assistance from the supporting institutions in this process is an important key and control, so that the newly formed organization remains on the right track.